Coating material and preparation method thereof, coated modified positive electrode material and preparation method thereof, and battery
By doping black phosphorus powder with sulfur powder and compounding with WO3 nanoparticles, the coating material was prepared, and the problem of insufficient performance of the ternary positive electrode material was solved, which significantly improved the conductivity and cyclic stability of the battery, and achieved energy density and Improvement of high-rate discharge performance.
Patent Information
- Application Number
- CN202411666845.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The electrochemical performance, thermal stability and structural stability of the ternary cathode material are insufficient, and modification is required to improve the performance of lithium-ion batteries.
The black phosphorus powder is doped with sulfur powder and compounded with WO3 nanoparticles. The coating material is prepared by heat treatment and hydrothermal reaction. Combined with the sintering process under an inert atmosphere, a coated modified positive electrode material is formed to improve conductivity and cycle stability. sex.
It significantly improves the conductivity and cyclic stability of the cathode material, enhances the energy density and high-rate discharge performance of the battery, while simplifying the preparation process and easy to produce on a large scale.
Smart Images

Figure CN119160955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to coating modification of positive electrode materials. Background Art
[0002] With the development of new energy vehicles, lithium-ion power batteries have attracted much attention as the most popular power battery for electric vehicles. Ternary cathode materials have high specific capacity, energy density and power density, making them a popular choice for commercial cathode materials. However, the electrochemical performance, thermal stability and structural stability of ternary cathode materials need to be further improved, and it is particularly important to study the modification of ternary cathode materials. Coating is a common modification method. The main function of coating is to act as a protective layer to isolate the direct contact between the electrolyte and the active electrode material, which greatly reduces a series of side reactions. By selecting different coating materials, the lithium ion conductivity and electronic conductivity of the ternary cathode material can be improved, and the lithium ion conductivity and electronic conductivity can be improved simultaneously through multiple coatings. Summary of the invention
[0003] The first object of the present invention is to provide a coating material for a lithium ion battery positive electrode material and a preparation method thereof.
[0004] The second object of the present invention is to provide a positive electrode material and a method for preparing the same.
[0005] A third object of the present invention is to provide a battery.
[0006] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0007] In a first aspect, the present invention provides a method for preparing a coating material, comprising the following steps: Step S1, ball-milling black phosphorus powder and sulfur powder, and then heat-treating them in an inert atmosphere to obtain sulfur-doped black phosphorus powder; Step S2, ultrasonically dispersing the sulfur-doped black phosphorus powder and WO3 nanoparticles in water, and then performing a hydrothermal reaction to obtain a coating material.
[0008] In a further preferred embodiment, the mass ratio of the black phosphorus powder to the sulfur powder is 1:0.001-10.
[0009] In a further preferred embodiment, the temperature of the heat treatment is 300-1000° C.; the time of the heat treatment is 1-10 h.
[0010] In a further preferred embodiment, the inert atmosphere is an argon atmosphere.
[0011] In a further preferred embodiment, the mass ratio of the sulfur-doped black phosphorus powder to the WO3 nanoparticles is 1:0.01-10.
[0012] In a further preferred embodiment, the temperature of the hydrothermal reaction is 100-200° C.; the time of the hydrothermal reaction is 0.1-8 h.
[0013] Based on the same inventive concept, the present invention provides a coating material prepared by the above preparation method.
[0014] In a second aspect, the present invention provides a coated modified positive electrode material, comprising a coating layer, wherein the material of the coating layer is the aforementioned coating material.
[0015] In a further preferred embodiment, the coated modified positive electrode material comprises a substrate, and the coating layer is located on at least a portion of the surface of the substrate; the substrate is a ternary positive electrode material.
[0016] The chemical formula of the substrate is preferably LiNi x Co y Mn z O2, where 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z =1.
[0017] The present invention also provides a method for preparing the positive electrode material, comprising: mixing the substrate and the coating material, and sintering them under an inert atmosphere.
[0018] In a further preferred embodiment, the inert atmosphere is an argon atmosphere.
[0019] In a further preferred embodiment, the mass ratio of the coating material to the substrate is 0.1:5-200; the sintering temperature is 300-1000° C.; and the sintering time is 2-12 hours.
[0020] In addition, the present invention provides a battery comprising the aforementioned coated and modified positive electrode material.
[0021] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The coating material provided by the invention can significantly improve the conductivity of the positive electrode material, and enhance the energy density, cycle stability and high-rate discharge performance of the battery.
[0022] The preparation method of the coating material of the present invention is simple, easy to operate and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an AFM image of the sulfur-doped black phosphorus powder obtained in step S1 of Example 1.
[0024] Figure 2 This is the SEM image of the coating material obtained in step S2 of Example 1.
[0025] Figure 3 The uncoated modified nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 SEM image of O2.
[0026] Figure 4 This is the SEM image of the coated and modified positive electrode material in Example 1.
[0027] Figure 5 This is the cycle performance diagram of the battery. DETAILED DESCRIPTION
[0028] In a first aspect, some embodiments of the present invention provide a method for preparing a coating material, comprising the following steps: Step S1, ball-milling black phosphorus powder and sulfur powder, and then heat-treating them in an inert atmosphere to obtain sulfur-doped black phosphorus powder; Step S2, ultrasonically dispersing the sulfur-doped black phosphorus powder and WO3 nanoparticles in water, and then performing a hydrothermal reaction to obtain a coating material.
[0029] In some specific embodiments, the mass ratio of the black phosphorus powder to the sulfur powder is 1:0.001-10, more preferably 1:0.01-5, and even more preferably 1:0.1-1.
[0030] In some specific embodiments, the heat treatment temperature is 300-1000° C., more preferably 400-600° C.; the heat treatment time is 1-10 h, more preferably 2-6 h.
[0031] In some specific embodiments, the inert atmosphere is an argon atmosphere.
[0032] In some specific embodiments, the mass ratio of the sulfur-doped black phosphorus powder to the WO3 nanoparticles is 1:0.01-10, and more preferably 1:0.1-2.
[0033] In some specific embodiments, the temperature of the hydrothermal reaction is 100-200° C., more preferably 120-160° C.; the time of the hydrothermal reaction is 0.1-8 h, more preferably 1-3 h.
[0034] Some embodiments of the present invention provide a coating material prepared by the above preparation method.
[0035] The analysis shows that: black phosphorus itself has a high electron mobility, and the doping of sulfur atoms can optimize the electronic structure of black phosphorus, reduce the barrier of electron transfer, and make the conductivity of black phosphorus higher; the doping of sulfur atoms can help the layered structure of black phosphorus to be more stable, reduce the van der Waals force between layers, and make it less likely for black phosphorus to slip or collapse during the cycle; sulfur-doped black phosphorus powder combines the dual characteristics of black phosphorus and sulfur. The layered structure and excellent conductivity of black phosphorus are combined with the high chemical reactivity of sulfur, so that sulfur-doped black phosphorus powder not only exhibits good electrical conductivity, but also has enhanced catalytic activity and surface regulation ability. WO3 has good ionic conductivity and chemical stability, providing a favorable channel for the migration of lithium ions and improving the ionic conductivity of the material. Further compounding sulfur-doped black phosphorus powder with WO3 nanoparticles to form a "dual channel" structure of electronic and ionic conductivity can improve the overall performance of the battery. In addition, WO3 itself has a strong antioxidant ability, which can effectively protect sulfur-doped black phosphorus from decomposition or oxidation in high temperature or oxidative environment.
[0036] In a second aspect, some embodiments of the present invention provide a coated modified positive electrode material, including a coating layer, wherein the material of the coating layer is the aforementioned coating material.
[0037] The coated modified positive electrode material comprises a substrate, and the coating layer is located on at least a portion of the surface of the substrate; the substrate is a ternary positive electrode material.
[0038] The chemical formula of the substrate is preferably LiNi x Co y Mn z O2, where 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z =1.
[0039] Some embodiments of the present invention also provide a method for preparing the above-mentioned positive electrode material, comprising: mixing a substrate and a coating material, and sintering them under an inert atmosphere.
[0040] In some specific embodiments, the mass ratio of the coating material to the substrate is 0.1:5-200, more preferably 0.1:50-150, and even more preferably 0.1:80-120.
[0041] In some specific embodiments, the inert atmosphere is an argon atmosphere.
[0042] In some specific embodiments, the sintering temperature is 300-1000° C., more preferably 500-700° C.; the sintering time is 2-12 h, more preferably 4-10 h.
[0043] In addition, the present invention provides a battery comprising the aforementioned coated and modified positive electrode material.
[0044] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0045] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0047] Example 1 Step S1, mixing black phosphorus powder and sulfur powder in a mass ratio of 1:0.1, placing the mixture in a ball mill and ball milling for 10 hours under an argon atmosphere at a ball milling speed of 300 rpm to obtain a ball milled product; placing the ball milled product in a tubular furnace and heat treating it in an argon environment at 500°C for 2 hours to obtain sulfur-doped black phosphorus powder.
[0048] Figure 1 This is an AFM image of sulfur-doped black phosphorus powder. It can be seen from the image that black phosphorus has a lamellar structure and that doped sulfur exists in the black phosphorus.
[0049] Step S2, sulfur-doped black phosphorus powder and WO3 nanoparticles are mixed in a mass ratio of 1:1, and then added to 100 mL of deionized water, and ultrasonicated for 30 minutes to obtain a mixed slurry. The mixed slurry is placed in a hydrothermal reactor and reacted at 140°C for 2 hours to obtain a composite. The composite is centrifuged, washed, and dried to obtain a coating material.
[0050] Figure 2 This is the SEM image of the coating material.
[0051] Step S3, mixing the coating material obtained in step S2 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 After mixing with O2 in a mass ratio of 1:90, the mixture was vacuum dried at 120°C for 12 hours and then sintered at 500°C for 5 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0052] Figure 3 LiNi is an uncoated and modified nickel-cobalt-manganese ternary cathode material. 0.9 Co 0.05 Mn 0.05 SEM image of O2, Figure 4 This is the SEM image of the coated modified positive electrode material. Figure 3 and Figure 4 It can be seen that compared with the smooth positive electrode material, the morphology of the positive electrode material coated with the coating material has obvious changes, and the surface is coated with obvious particles.
[0053] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that there is no step S2. Specifically: Step S1, mixing black phosphorus powder and sulfur powder in a mass ratio of 1:0.1, placing the mixture in a ball mill and ball milling for 10 hours under an argon atmosphere at a ball milling speed of 300 rpm to obtain a ball milled product; placing the ball milled product in a tubular furnace and heat treating it in an argon environment at 500°C for 2 hours to obtain sulfur-doped black phosphorus powder.
[0054] Step S2, mixing the sulfur-doped black phosphorus powder obtained in step S1 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 After mixing with O2 in a mass ratio of 1:90, the mixture was vacuum dried at 120°C for 12 hours and then sintered at 500°C for 5 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0055] Comparative Example 2 WO3 nanoparticles and LiNi 0.9 Co 0.05 Mn 0.05 After mixing with O2 in a mass ratio of 1:90, the mixture was vacuum dried at 120°C for 12 hours and then sintered at 500°C for 5 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the black phosphorus is not doped with sulfur.
[0057] Step S1, black phosphorus powder and WO3 nanoparticles are mixed in a mass ratio of 1:1, and then added to 100 mL of deionized water, and ultrasonicated for 30 minutes to obtain a mixed slurry. The mixed slurry is placed in a hydrothermal reactor and reacted at 180°C for 8 hours to obtain a composite. The composite is centrifuged, washed, and dried to obtain a coating material.
[0058] Step S2, mixing the coating material obtained in step S1 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 After mixing with O2 in a mass ratio of 1:90, it was dried at 120°C for 12 hours and then sintered at 500°C for 5 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0059] Comparative Example 4 Black phosphorus powder and nickel-cobalt-manganese ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 After mixing with O2 in a mass ratio of 1:90, it was dried at 120°C for 12 hours and then sintered at 500°C for 5 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0060] Example 2 Step S1, mixing black phosphorus powder and sulfur powder in a mass ratio of 1:0.001, placing the mixture in a ball mill and milling it for 2 hours under an argon atmosphere at a ball milling speed of 100 rpm to obtain a ball milled product; placing the ball milled product in a tubular furnace and heat treating it in an argon environment at 300°C for 1 hour to obtain sulfur-doped black phosphorus powder.
[0061] Step S2, sulfur-doped black phosphorus powder and WO3 nanoparticles are mixed in a mass ratio of 1:0.01, and then added to 20 mL of deionized water, and ultrasonicated for 10 minutes to obtain a mixed slurry. The mixed slurry is placed in a hydrothermal reactor and reacted at 100° C. for 8 hours to obtain a composite. The composite is centrifuged, washed, and dried to obtain a coating material.
[0062] Step S3, mixing the coating material obtained in step S2 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.7 Mn 0.3 After mixing with O2 at a mass ratio of 0.1:200, it was dried at 100°C for 2 hours and then sintered at 300°C for 10 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0063] Example 3 Step S1, mixing black phosphorus powder and sulfur powder in a mass ratio of 1:10, placing the mixture in a ball mill and ball milling for 10 hours in an argon atmosphere at a ball milling speed of 500 rpm to obtain a ball milled product; placing the ball milled product in a tubular furnace and heat treating it in an argon environment at 1000°C for 10 hours to obtain sulfur-doped black phosphorus powder.
[0064] Step S2, sulfur-doped black phosphorus powder and WO3 nanoparticles are mixed in a mass ratio of 1:10, and then added to 200 mL of deionized water, and ultrasonicated for 60 minutes to obtain a mixed slurry. The mixed slurry is placed in a hydrothermal reactor and reacted at 200°C for 1 hour to obtain a composite. The composite is centrifuged, washed, and dried to obtain a coating material.
[0065] Step S3, mixing the coating material obtained in step S2 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.7 Co 0.2 Mn 0.1After mixing with O2 in a mass ratio of 0.1:5, it was dried at 120°C for 10 hours and then sintered at 700°C for 10 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0066] Example 4 Step S1, mixing black phosphorus powder and sulfur powder in a mass ratio of 1:1, placing the mixture in a ball mill and ball milling for 5 hours under an argon atmosphere at a ball milling speed of 250 rpm to obtain a ball milled product; placing the ball milled product in a tubular furnace and heat treating it in an argon environment at 600°C for 4 hours to obtain sulfur-doped black phosphorus powder.
[0067] Step S2, mixing sulfur-doped black phosphorus powder and WO3 nanoparticles at a mass ratio of 1:0.5, then adding them to 100 mL of deionized water, and ultrasonicating for 30 minutes to obtain a mixed slurry. The mixed slurry is placed in a hydrothermal reactor and reacted at 160°C for 3 hours to obtain a composite. The composite is centrifuged, washed, and dried to obtain a coating material.
[0068] Step S3, mixing the coating material obtained in step S2 with the nickel-cobalt-manganese ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 After mixing with O2 in a mass ratio of 0.1:100, it was dried at 110°C for 5 hours and then sintered at 500°C for 6 hours in an argon atmosphere to obtain a coated modified positive electrode material.
[0069] The coated modified positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-4 and LiNi 0.9 Co 0.05 Mn 0.05 O2 assembled into a battery: The positive electrode material, Super-P, KS-6 and polyvinylidene fluoride (PVDF) were mixed in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 89:5:3.5:2.5 to prepare a uniform positive electrode slurry. The prepared positive electrode slurry was evenly coated on aluminum foil, and a fast coater was used to ensure uniform coating, and then dried in a vacuum environment at 120°C for 2 hours to ensure that NMP was completely volatilized and a dry positive electrode material layer was obtained to obtain a positive electrode sheet. The positive electrode sheet was cut into discs (12-15 mm diameter) suitable for button batteries.
[0070] Metal lithium sheet was used as the negative electrode, Celgard-2400 separator was used as the diaphragm, 1M LiPF6 dissolved in EC+DMC+EMC (volume ratio 1:1:1) solution was used as the electrolyte, and aluminum foil was used as the positive electrode current collector.
[0071] Place the negative electrode shell on the assembly table; place the metal lithium negative electrode sheet into the negative electrode shell; place the Celgard-2400 diaphragm on the negative electrode sheet to ensure tight coverage; drip an appropriate amount of electrolyte on the diaphragm to ensure that the diaphragm and the negative electrode sheet are fully soaked; place the dried positive electrode sheet on top of the diaphragm; drip a small amount of electrolyte on the positive electrode sheet; place the metal gasket and spring sheet in order to ensure close contact inside; place the positive electrode shell on the top; use a button battery packaging machine for packaging to ensure that the battery is sealed to avoid electrolyte leakage.
[0072] Test battery: Test temperature is 25℃, operating voltage range is 3.0-4.3 V, cycled at 0.1C for 2 cycles, then cycled at 0.5C for 50 cycles.
[0073] Test results such as Figure 5 shown.
[0074] Comparison of the coated modified positive electrode material obtained in Example 1 and the uncoated modified LiNi 0.9 Co 0.05 Mn 0.05 The cycle performance of the battery assembled with O2 showed that the initial discharge capacity of the two was roughly at the same level, but during the cycle, the uncoated modified LiNi 0.9 Co 0.05 Mn 0.05 The discharge specific capacity of the battery assembled with O2 drops sharply, but the capacity retention rate of the battery assembled with the coated and modified positive electrode material obtained in Example 1 is very good.
[0075] By comparing the cycle performance of the battery assembled with the coated modified positive electrode material obtained in Example 1 and the coated modified positive electrode material obtained in Comparative Examples 1-4, it is found that the battery assembled with the black phosphorus coated modified positive electrode material alone has the worst cycle performance and a very low capacity retention rate (Comparative Example 4); the battery assembled with the black phosphorus (undoped with sulfur) and WO3 composite material coated modified positive electrode material has relatively good cycle performance (Comparative Example 3); the battery assembled with the coated modified positive electrode material obtained in Example 1 has the best cycle performance and the highest initial discharge specific capacity. The battery assembled with the coated modified positive electrode material obtained in Examples 2-4 also has excellent cycle performance.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a coating material, characterized in that: The following steps are involved: Step S1, ball-milling black phosphorus powder and sulfur powder, and then heat-treating them in an inert atmosphere to obtain sulfur-doped black phosphorus powder; Step S2, ultrasonically dispersing the sulfur-doped black phosphorus powder and WO3 nanoparticles in water, and then performing a hydrothermal reaction to obtain a coating material.
2. The method for preparing the coating material according to claim 1, characterized in that: The mass ratio of the black phosphorus powder to the sulfur powder is 1:0.001-10.
3. The method for preparing the coating material according to claim 1, characterized in that: The temperature of the heat treatment is 300-1000° C.; the time of the heat treatment is 1-10 hours.
4. The method for preparing the coating material according to claim 1, characterized in that: The mass ratio of the sulfur-doped black phosphorus powder to the WO3 nanoparticles is 1:0.01-10.
5. The method for preparing the coating material according to any one of claims 1 to 4, characterized in that: The temperature of the hydrothermal reaction is 100-200° C.; the time of the hydrothermal reaction is 0.1-8 hours.
6. A coating material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.
7. A coated modified positive electrode material, characterized in that: It comprises a substrate and a coating layer, wherein the coating layer is located on at least a portion of the surface of the substrate; the substrate is a ternary positive electrode material, and the material of the coating layer is the coating material according to claim 6.
8. The method for preparing the coated modified positive electrode material according to claim 7, characterized in that: include: The substrate and the coating material are mixed and sintered under an inert atmosphere.
9. The method for preparing the coated modified positive electrode material according to claim 8, characterized in that: The mass ratio of the coating material to the substrate is 0.1:5-200; the sintering temperature is 300-1000°C; and the sintering time is 2-12h.
10. A battery, characterized in that: Including the coated and modified positive electrode material as described in claim 7.
Citation Information
Patent Citations
Lithium secondary battery lithium-rich cathode composite and preparation method thereof
CN105870438A
Mesoporous nano tungsten oxide coated NCA cathode material and preparation method thereof and lithium ion battery
CN109244411A
Phosphorus-based composite material as well as preparation method and application thereof
CN114759177A
Black phosphorus composite material, antibacterial nanofiber material, preparation method and application
CN116084041A
Doped and coated ternary positive electrode material as well as preparation method and application thereof
CN116960310A
